Effect of heavy metal impurities in secondary Mg alloys on the microstructure and mechanical properties during deformation. (January 2015) - Al-Samman, T.
Highlights: Increased content of impurities showed improvement of strength during deformation. The mechanical response depends on the impurities rather than the alloy mixture. Deformation at highest Z exhibited shear banding, twinning and partial DRX. Deformation at lowest Z exhibited complete DRX and texture weakening. The texture and mechanical properties were not impaired by the impurities. Abstract: The main problem of recycling and remelting of magnesium scrap is the achievement of a high purity quality product with appropriate strength and corrosion properties. The current work was carried out to examine whether a high level of Cu and Ni impurities in Mg–Al based alloys is permissible from a mechanical performance standpoint. Defining the proper composition range, impurity limits and the property profile are key issues for future alloy design of economic and high performance magnesium products. The produced experimental alloys were thermo-mechanically processed by hot extrusion and subsequently deformed in plane strain compression at various temperatures and strain rate to determine the stress–strain response and characterize the resulting microstructures and textures, which served as basis for comparison between the standard and contaminated alloys.